Barrett's Esophagus - Yong Kang Lee (Yong Chan Lee, 2022)
Barrett's esophagus (BE) is caused by metaplasia of squamous epithelium into columnar epithelium, mainly in the lower esophagus. Updates have been made in the etiology, diagnosis and treatment of BE since its first report as an ulcerative lesion in the lower esophagus. Columnar metaplasia of the lower esophagus has been reported as a result of gastroesophageal reflux, rather than genetic factors. When specialized intestinal metaplasia (SIM) is confirmed on biopsy, it is diagnosed as BE; otherwise, it is described as columnar line esophagus (CLE). Recent recommendations state that the following two conditions must be satisfied to diagnose BE: CLE with a length ≥1 cm proximal to the gastroesophageal junction, or SIM, with goblet cells confirmed on biopsy. BE is a key risk factor for esophageal adenocarcinoma. Early detection and treatment of BE, dysplasia, and early esophageal adenocarcinoma arising from BE has become a critical issue in the USA and Europe. The prevalence of BE in Korea is likely to increase because of the increasing prevalence of gastroesophageal reflux diseases. However, there are few reports on the diagnosis and treatment of BE in Korea. In this narrative review, important historical discoveries related to BE, the anatomical structures and endoscopic findings around the gastroesophageal junction required for diagnosing CLE and BE, and a brief review of the guidelines for the diagnosis and treatment of BE are summarized.